A systematic comparison of obsidian hydration measurements: The first application of micro-image with secondary ion mass spectrometry to the prehistoric obsidian. (10th January 2020) - Nakazawa, Yuichi; Kobayashi, Sachio; Yurimoto, Hisayoshi; Akai, Fumito; Nomura, Hidehiko
Abstract: Archaeologists have long used obsidian hydration dating method to give chronometric dates for obsidian artifacts. Models using these equations independently employ different measurement systems, which are based on rim thicknesses determined by optical microscope and hydrogen depths measured by secondary ion mass spectrometry (SIMS), respectively, although the inconsistency of both measurements has been reported. Firstly, this paper describes a systematic comparison that was done on optical rim thicknesses and hydrogen depths by means of an isotope microscope, which provides micro-imaging with SIMS. Depth profiles of hydrogen were precisely obtained from the spots where optical measurements were taken on the archaeological obsidian flakes from two distinctive cultural horizons (older: Upper Paleolithic, younger: Initial Jomon) in the stratified open-air site of Jozuka in southern Kyushu (Japan). Secondarily, using the measurements of hydrogen depths that are the most consistent to the measurements of optical thicknesses, the estimated hydration rate of the Holocene (Initial Jomon) is slower than that of the Late Pleistocene (Upper Paleolithic), implying that the difference in hydration rates was due to the difference of intrinsic water content of obsidian and/or obsidian geochemistry. An application of micro-imaging with SIMS to measure hydrogen depths on obsidian shows promise as a tool for improving the practice of hydration dating and evaluating local climatic condition.